ANALISA PENYELESAIAN MASALAH DAN PERBAIKAN ALAT PATIENT MONITOR DI RSUP H. ADAM MALIK MEDAN - Priyulida, Fitria; Manurung, Kesaktian; Maulana, Fazri; Malau, Riris (Prodi Teknik Elektromedik Universitas Sari Mutiara Indonesia, 2023)
Research on patient monitor tools has been carried out. The purpose of this study was to determine the problem of repairing the patient monitor tool. Corrective maintenance is maintenance action taken to overcome damage or congestion that occurs repeatedly, then take corrective action on the tool. Patient monitor is a tool that is used to monitor the patient's physiological condition. The purpose of this study is Troubleshooting (damage) patient monitor tools. Improvements to the patient monitor tool with the results of the study found that troubleshooting was seen through the results of less accurate blood pressure calculations so that it affected the diagnosis process in NIBP (Non Invasive Blood Pressure), Spo2 (Oxygen Pressure Saturation) patients. Incorrect reading of SpO2 results can be affected by sensor damage which when diagnosing patients, Ecg (Electrocardiograph) affects the results of diagnostics made by the instrument on patients, Misdiagnosis can occur due to incorrect placement of electrodes/tappers, damaged electrodes, Temperature (temperature) on the temperature sensor, namely damage to the temperature connector cable and the occurrence of undetected temperature results on the patient monitor tool. The research is that the patient monitor has been functioning properly after checking and repairing. Maintenance of the patient monitor must be routine and scheduled to prevent damage so that the age of use of tools and accessories is longer. Testing and calibration of patient monitor tools, especially on patient monitor parameters, must carry out routine checks on patient monitors, especially patient monitor accessories.